Turkish Tombul hazelnut (Corylus avellana L.) protein concentrates: functional and rheological properties - Tatar, F.; Tunc, M. T.; Kahyaoglu, T. (SPRINGER INDIA, 2015)
Turkish Tombul hazelnut consumed as natural or processed forms were evaluated to obtain protein concentrate. Defatted hazelnut flour protein (DHFP) and defatted hazelnut cake protein (DHCP) were produced from defatted hazelnut flour (DHF) and defatted hazelnut cake (DHC), respectively. The functional properties (protein solubility, emulsifying properties, foaming capacity, and colour), and dynamic rheological characteristics of protein concentrates were measured. The protein contents of samples varied in the range of 35-48 % (w/w, db) and 91-92 % (w/w, db) for DHF/DHC and DHFP/DHCP samples, respectively. The significant difference for water/fat absorption capacity, emulsion stability between DHF and DHC were determined. On the other hand, the solubility and emulsion activity of DHF and DHC were not significantly different (p>0.05). Emulsion stability of DHFP (% 46) was higher than that of DHCP (% 35) but other functional properties were found similar. According to these results, the DHCP could be used as DHFP in food product formulations. The DHFP and DHCP samples showed different apparent viscosity at the same temperature and concentration, the elastic modulus (G' value) of DHPC was also found higher than that of DHFP samples.
Keywords: Hazelnut; Functionality; Protein concentrate; Rheology; NUT ANACARDIUM-OCCIDENTALE; ELECTROPHORETIC CHARACTERIZATION; CHEMICAL-COMPOSITION; SOLUBILIZATION; DIGESTIBILITY; CULTIVARS; ISOLATE; COWPEA; FLOUR; SEED; Food Science & Technology